Comparative Genomics Between Rice and Arabidopsis Shows Scant Collinearity in Gene Order - Liu, Hong; Sachidanandam, Ravi; Stein, Lincoln (Genome Research, 2001)
We have investigated possible collinearity between the genomes of rice and Arabidopsis by comparing 126 annotated and mapped rice BAC sequences (∼20 Mb of sequence) with the annotated and complete Arabidopsis genome (∼115 Mb). Although we were able to identify several regions in which gene order is preserved, they are relatively small, and are interrupted by noncollinear genes. Computer simulation showed that these microscale collinearities are above the expectation for a random process. On the other hand, the order of exons within homologous genes (<2.5 kb) was preserved, as expected.
10.1101/gr.194501